2011
DOI: 10.1038/bjc.2011.386
|View full text |Cite
|
Sign up to set email alerts
|

Cold plasma selectivity and the possibility of a paradigm shift in cancer therapy

Abstract: Background:Plasma is an ionised gas that is typically generated in high-temperature laboratory conditions. However, recent progress in atmospheric plasmas has led to the creation of cold plasmas with ion temperature close to room temperature.Methods:Both in-vitro and in-vivo studies revealed that cold plasmas selectively kill cancer cells.Results:We show that: (a) cold plasma application selectively eradicates cancer cells in vitro without damaging normal cells; and (b) significantly reduces tumour size in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
541
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 678 publications
(577 citation statements)
references
References 22 publications
19
541
0
2
Order By: Relevance
“…The in vitro work covered a host of cancerous cell lines, which included glioblastoma, melanoma, papilloma, carcinoma, colorectal cancer, ovarian cancer, prostate cancer cells, squamous cell carcinoma, leukemia, and lung cancer. The in vivo (animal model) work can be found in [38,44,45,53].…”
Section: Ltp Takes On Hygiene and Medical Challengesmentioning
confidence: 99%
“…The in vitro work covered a host of cancerous cell lines, which included glioblastoma, melanoma, papilloma, carcinoma, colorectal cancer, ovarian cancer, prostate cancer cells, squamous cell carcinoma, leukemia, and lung cancer. The in vivo (animal model) work can be found in [38,44,45,53].…”
Section: Ltp Takes On Hygiene and Medical Challengesmentioning
confidence: 99%
“…The utilization of various exogenous agents from natural products like Indonesian honey 2 and oleic or linoleic acid 3 to physical tools like light 4 and laser 5 hasbeen shown to enhance the overlapping healing phases, including inflammation, proliferation and remodeling 1 . Among these, wound therapy based on cold plasma, that is, nonequilibrium plasma (with an electron temperature much higher than the gas temperature), with a low temperature of ionized gas 6 , has opened the possibility of a paradigm shift in biomedical therapy 7 ;it has drawn substantial attention from both plasma and wound care scientists since its feasibility to work through living tissue 8,9 and its potency for resolving problems in contemporary wound care were demonstrated 10 . As the fourth state of matter 6 , plasma has the ability to produce controllable reactive species, like nitric oxide (NO) and hydroxyl radicals (OH), upon contacting the open air 11 , as well as OH radicals and hydrogen peroxide (H 2 O 2 ) upon contacting an aqueous solution 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Specific applications include (but are not limited to): wound treatment, tissue engineering [209], treatment of skin diseases such as Rosacea [210], antimicrobial applications [211], inducing cancer cell apoptosis [212] and minimizing adenovirus infectivity [213]. In particular, it has also been recently shown that cold plasmas may be used to selectively kill cancer cells without damaging surrounding healthy cells [214]. Kong et al noted that the synergies between cold atmospheric plasmas and charged nanoparticles addressed the issues of reactivity, selectivity, toxicity and penetration required for effective drug delivery and medical treatment [208].…”
Section: Existing and Emerging Applicationsmentioning
confidence: 99%